The Javanese Culturally-Bound Aspects in the “Java Heat” Movie - Bahruddin Bahruddin (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2015)
This research is to find the Javanese culturally-bound aspects in the “Java Heat” movie. This research uses descriptive qualitative method with the library research approach. From this research, the researcher finds that the Javanese culturally-bound aspects found include some components of the Javanese and those appear to support the movie in exposing the Javanese culture. Moreover, this also shows some Javanese philosophy and moral message. The Javanese culturally-bound aspects include the use of some particular clothes, accessories, the place, the detail color and motif, the place exposed, and the show exposed.